High-temperature modification of steel slag using composite modifier containing silicon calcium slag, fly ash, and reservoir sediment - Yuan, Dongxia; Liang, Xiaoying; Gao, Ying; Ping, Haoyan; Wang, Changlong; Ma, Jintao; Zheng, Yongchao; Jing, Jianlin; Qi, Yang; Zhai, Yuxin; Liu, Feng (Frontiers in Earth Science, 2023)
Steel slag (SS) is a kind of industrial solid waste, and its accumulation brings certain harm to the ecological environment. In order to promote the building material utilization of SS, high-temperature modification (HTM) of SS is performed using a composite modifier (CMSFR) containing silicon calcium slag (SCS), fly ash (FA), and reservoir sediment (RS). Then, the authors investigated the effect of CMSFR on the cementitious properties and volume soundness of SS mixture after HTM (SMHTM). After that, the mineral composition and microstructure of SMHTM were investigated through X-ray fluorescence analysis (XRF), X-ray diffraction (XRD), scanning electronic microscopy (SEM), energy dispersive spectrometry (EDS), and particle size analysis. It was found that the free CaO (f-CaO) content obviously decreased, and the cementitious properties improved in SMHTM. When the CMSFR content was 20% (SCS: FA: RS = 9:7:4), and the modification temperature (MT) was 1,250 o C, the mass fraction of f-CaO in SMHTM dropped from 4.81% to 1.90%, down by 60.5%; the 28-day activity index of SMHTM increased to 85.4%, 14.3% higher than that of raw SS, which meets the technical requirement of Steel slag powder used for cement and concrete (GB/T 20491-2017): the activity index of grade I SS powder must be greater than or equal to 80%. As the mass fraction of CMSFR grew from 10% to 30%, new mineral phases formed in SMHTM, including diopside (CMS2), ceylonite (MgFe2O4), gehlenite (C2AS), tricalcium aluminate (C3A), and magnetite (Fe3O4). The HTM with CMSFR promotes the decomposition of RO phase (a continuous solid solution composed of divalent metal oxides like FeO, MgO, MnO, and CaO) in raw SS, turning the FeO in that phase into Fe3O4. The above results indicate that the SMHTM mixed with CMSFR can be applied harmless in cement and concrete, making low-energy fine grinding of SS a possibility.